2013
DOI: 10.1073/pnas.1221442110
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-based facial amphiphiles for stabilization and crystallization of membrane proteins

Abstract: Amphiphile selection is a critical step for structural studies of membrane proteins (MPs). We have developed a family of steroidbased facial amphiphiles (FAs) that are structurally distinct from conventional detergents and previously developed FAs. The unique FAs stabilize MPs and form relatively small protein-detergent complexes (PDCs), a property considered favorable for MP crystallization. We attempted to crystallize several MPs belonging to different protein families, including the human gap junction chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 51 publications
2
89
0
Order By: Relevance
“…When the concentration of phosphate was lowered to prevent formation of insoluble phosphates, a screen of several metal ions indicated that zinc ions produced crystals most consistently. Additionally, exchange of CHAPS used during purification with a facial amphiphile developed by Qinghai Zhang and co-workers (15) at The Scripps Research Institute increased the size of the crystals. In the presence of thioridazine, Façade-EM, and zinc ions, P450 2D6 crystallized in a new lattice exhibiting the P212121 space group with four molecules in the asymmetric unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the concentration of phosphate was lowered to prevent formation of insoluble phosphates, a screen of several metal ions indicated that zinc ions produced crystals most consistently. Additionally, exchange of CHAPS used during purification with a facial amphiphile developed by Qinghai Zhang and co-workers (15) at The Scripps Research Institute increased the size of the crystals. In the presence of thioridazine, Façade-EM, and zinc ions, P450 2D6 crystallized in a new lattice exhibiting the P212121 space group with four molecules in the asymmetric unit.…”
Section: Resultsmentioning
confidence: 99%
“…For crystallization of the thioridazine complex in the presence of zinc chloride, the phosphate concentration was lowered to 25 mM, and the detergent CHAPS was replaced by a new facial amphiphile FA-3 (15), which is now commercially available as Facade™-EM (Avanti Polar Lipids), by using 5 rounds of 5ϳ10-fold dilution with 25 mM KPi buffer, pH 7.4, containing 20% glycerol, 0.1 mM thioridazine, 10 mM ␤-mercaptoethanol, 3 The abbreviations used are: PDB, Protein Data Bank; F o , observed structure factor; F c , calculated structure factor; RTZ, R enantiomer of thioridazine. and 0.4 mM Façade-EM and followed by concentration using an Amicon centrifugal filtration unit (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…The cell lines used to express Escherichia coli were JM109 and TOPP3 cells purchased from Stratagene (La Jolla, CA). 3a- ethyl)phosphoryl)ethyloxy)-cholane (FA-7/234-chol) is a facial amphiphile used as described previously (Lee et al, 2013). D-Aminolevulinic acid, phenylmethylsulfonyl fluoride (PMSF), lysozyme, dithiothreitol (DTT), 2-mercaptoethanol (BME), and TCEP (tris(2-carboxyethyl) phosphine) were from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore the steroid-based facial amphiphiles (FA) are another type of solubilization/stabilization agents being actively developed. They utilize the cholate scaffold, to which (typically) sugar headgroups are attached [82,83]. Such design proved to be useful to not only to stabilize membrane proteins (via tight interactions between a membrane proteins and FA owning to the large hydrophobic surface of the latter), but to also improve their crystallization (via the formation of more compact protein-detergent complexes, which can pack more tightly in a crystal, owing to the ability of FA to mediate intermolecular contacts between molecules of membrane proteins) [84].…”
Section: Discussion and Outlookmentioning
confidence: 99%